The Ability of Different Ketohexoses to Alter Apo-A-I Structure and Function In Vitro and to Induce Hepatosteatosis, Oxidative Stress, and Impaired Plasma Lipid Profile in Hyperlipidemic Zebrafish. (21st May 2018) - Yadav, Dhananjay; Kim, Suk-Jeong; Bae, Myung Ae; Kim, Jae-Ryong; Cho, Kyung-Hyun
Abstract : In the current study, we have tested the nonenzymatic glycation activities of ketohexoses, such as tagatose and psicose. Although tagatose-treated apoA-I (t-A-I) and psicose-treated apoA-I (p-A-I) exerted more inhibitory activity you cupric ion-mediated low-density lipoprotein (LDL) oxidation and oxidized LDL (oxLDL) phagocytosis into macrophage than fructose-treated apoA-I (f-A-I). In the lipid-free state, t-A-I and f-A-I showed more multimerized band without crosslinking. Since t-A-I lost its phospholipid binding ability, the rHDL formation was not as successful as f-A-I. However, injecting t-A-I showed more antioxidant activities in zebrafish embryo under the presence of oxLDL. Three weeks of consumption of fructose (50% of wt in Tetrabit/4% cholesterol) showed a 14% elevation of serum triacylglycerol (TG), while tagatose-administered group showed 30% reduction in serum TG compared to high cholesterol control. Fructose-fed group showed the biggest area of Oil Red O staining with the intensity as strong as the HCD control. However, tagatose-consumed group showed much lesser Oil Red O-stained area with the reduction of lipid accumulation. In conclusion, although tagatose treatment caused modification of apoA-I, the functional loss was not as much severe as the fructose treatment in macrophage cell model, zebrafish embryo, and hypercholesterolemic zebrafish model.